2000
DOI: 10.1051/analusis:2000280801
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the incidence of intersex fish in Seine-Maritime and Sussex region

Abstract: The incidence of intersex was examined in freshwater fish in one English and three French rivers. Over 331 fish, mainly roach, were sampled above and below the major sewage treatment works (STW) on each river and the incidence of intersex was recorded by histological examination of fish gonads. No intersex conditions were observed in male fish collected either above or below the major STW on the River Ouse in Sussex. In contrast, roach showing primary oocytes in their testes were found in all three French rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 17 publications
2
43
0
1
Order By: Relevance
“…Rutilus rutilus, Xiphias gladius, Acipenser gueldenstaedtii) and invertebrate species, as Mya arenaria, marine and freshwater mussels (e.g. Mytilus galloprovincialis, Tapes philippinarium, Elliptio complanata) (Minier et al 2000;Jobling et al 2002;De Metrio et al 2003;Gagné and Blaise 2003;Canesi et al 2004;Langston et al 2005;Sumpter 2005;Bjerregaard et al 2006;Jackson et al 2006;Porte et al 2006;Almeida et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Rutilus rutilus, Xiphias gladius, Acipenser gueldenstaedtii) and invertebrate species, as Mya arenaria, marine and freshwater mussels (e.g. Mytilus galloprovincialis, Tapes philippinarium, Elliptio complanata) (Minier et al 2000;Jobling et al 2002;De Metrio et al 2003;Gagné and Blaise 2003;Canesi et al 2004;Langston et al 2005;Sumpter 2005;Bjerregaard et al 2006;Jackson et al 2006;Porte et al 2006;Almeida et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…In single cases alkylphenols compounds have also been suggested as possible causative agents (Sheahan et al 2002). Induction of vitellogenin (vtg), a biomarker of estrogenic exposure, has been detected in various species of male fish collected downstream of sewage treatment works (STWs) (Jobling et al 1998;Flammarion et al 2000;van Aerle et al 2001;Gercken and Sordyl 2002;Hecker et al 2002;Folmar et al 2001;Harshbarger et al 2000;Minier et al 2000) and in caged fish placed near STW outlets (Harries et al 1997(Harries et al , 2000Larsson et al 1999). After high prevalences of intersex were first observed in roach (Rutilus rutilus) from UK rivers (Jobling et al 1998), other populations of fish with intersex males have been observed downstream of STWs (van Aerle et al 2001;Aravindakshan et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Reproductive disorders among wild populations of fish also include abnormal hormone levels (Folmar et al 1996(Folmar et al , 2002Jobling et al 2002a;Lavado et al 2004), asynchrony in the development of germ cells in males and females as well as reduced spawning and fertilising capacity of male fish (Aravindakshan et al 2004;Jobling et al 2002a, b). Observed feminisation in wild populations of fish does now include the freshwater species roach (Jobling et al 1998: Minier et al 2000, gudgeon (Gobio gobio) (van Aerle et al 2001), carp (Cyprinus carpio) (Folmar 1996;Solé et al 2002a, b), bream (Abramis brama L.) (Hecker et al 2002;Vethaak et al 2002), chub (Leucicus cephalus) (Flammarion et al 2000), shovelnose sturgeon (Scaphirhychus platyorynchus) (Harshbarger et al 2000), walleye (Stizostedion vitreum) (Folmar et al 2001), three spined stickleback (Gasterosteus aculeatus) and perch (Perca fluviatilis) (Gercken and Sordyl 2002) plus the marine species flounder (Platichthys flesus) (Lye et al 1997(Lye et al , 1998Allen et al 1999;Stentiford et al 2003), eelpout (Zoarces viviparus) (Mathiessen et al 2002;Stentiford et al 2003) and two species of sand gobies (Pomatoschistus minutes and P. lozanoi) (Mathiessen et al 2002). Many of the freshwater species which have been examined for signs of feminisation belong to the carp family.…”
Section: Introductionmentioning
confidence: 99%
“…However, the condition has now been detected in several wild freshwater and migratory species, including roach Rutilus rutilus (Jafri & Ensor 1979, Purdom et al 1994, Jobling et al 1998, gudgeon Gobio gobio (van Aerle et al 2001), barbel Barbus plebejus (Vigano et al 2001), chub Leuciscus cephalus (Minier et al 2000), bream Abramis brama (Slooff & Kloowijk-Vandijk 1982), white perch Morone americana (Kavanagh et al 2002), stickleback Gasterosteus aculeatus (authors' pers. obs.…”
Section: Introductionmentioning
confidence: 99%